A Pedagogical Approach To Developing Cognitive Skills In 4–5-Year-Old Children Through Children’s Folklore - Odina Nabiyevna Fozilova (International Scientific and Current Research Conferences, 2026)
The study examines the pedagogical potential of counting rhymes as a genre of children’s folklore for supporting cognitive development in 4–5-year-old children. Particular attention is paid to the relationship between the structural characteristics of counting rhymes –rhythm, repetition, sequentiality, verbal-motor coordination, and rule-based performance –and such cognitive processes as attention, memory, perception, and self-regulation. The study employs theoretical content analysis, comparative analysis, and pedagogical modelling. The findings of the theoretical analysis suggest that counting rhymes may be pedagogically organized not only as material for memorization and reproduction but also as a means of stimulating sequential memory, voluntary attention, verbal-motor coordination, and rule-governed behaviour. A transition from reproductive performance to productive cognitive activity is proposed as a methodological principle for the use of counting rhymes in preschool education.